2020
DOI: 10.1002/jgm.3168
|View full text |Cite
|
Sign up to set email alerts
|

miR‐511 inhibits proliferation and metastasis of breast cancer cells by targeting FGF4

Abstract: Background The present study aimed to explore the functions and molecular mechanisms of miR‐511 in breast cancer. Methods A quantitative real‐time polymerase chain reaction (qRT‐PCR) was used to detect miR‐511 levels in breast cancer tissues; a chi‐squared test was used to analyze the relationship between miR‐511 expression level and pathological parameters of breast cancer patients; the proliferation of breast cancer cell lines MDA‐MB‐231 and MCF‐7 was determined by the cell counting kit‐8 (CCK‐8) assay; migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The expression of MiR-32 is markedly lower in ovarian cancer tissues than that in adjacent normal tissues; miR-32 also directly targets the 3′-UTR of BTLA ( 123 ). BTLA is a new member of the CD28 family ( 34 ).…”
Section: The Impact Of Mirna Targeting Btla On Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of MiR-32 is markedly lower in ovarian cancer tissues than that in adjacent normal tissues; miR-32 also directly targets the 3′-UTR of BTLA ( 123 ). BTLA is a new member of the CD28 family ( 34 ).…”
Section: The Impact Of Mirna Targeting Btla On Cancermentioning
confidence: 99%
“…Previous research showed that miR-32 can suppress the malignant behavior of HeLa cells ( 124 ). Moreover, the high expression level of BTLA could significantly play an anticancer role in miR-32, while the overexpression of miR-32 could greatly inhibit the mRNA and protein expressions of BTLA ( 123 ). A negative feedback loop was formed between miR-32 and BTLA, regulating the malignant behavior of ovarian cancer cells ( 123 ).…”
Section: The Impact Of Mirna Targeting Btla On Cancermentioning
confidence: 99%
“…MiR-NAs have been recognized as the main regulators of cancer development as well. For instance, miR-511 was described to suppress breast cancer cell proliferation and invasion through targeting FGF4 [21]. In this study, we found miR-3196 could bind with MAFG-AS1.…”
Section: Discussionmentioning
confidence: 51%
“…Another explanation might be that as many different miRs are upregulated in CLL cells, they can also be responsible for abnormal BTLA expression and in consequence could partially mask the effect of miR-155-5p inhibition. Until now only miR-32 has been described to regulate BTLA expression [ 48 ], thus, we cannot exclude the influence of other miRs on BTLA expression in CLL cells. Silencing of miR-155-5p did not have significant influence on BTLA expression in the case of HC B cells.…”
Section: Discussionmentioning
confidence: 99%